Metabolomics Analysis of the Mechanism of Yuquan Capsules in the Treatment of T2DM Rats Using UPLC/MS - Zhang M; Tan Z; Ou M; Li T; Yang X; Chen L; Xiao R; Lu N; Wang X; Wu F (Diabetes, Metabolic Syndrome and Obesity)
Mengli Zhang,1,* Zhien Tan,1 Min Ou,1 Taiping Li,1,2 Xiaonan Yang,1 Lu Chen,1 Rui Xiao,3 Na Lu,1 Xijun Wang,2 Fangfang Wu1,3,* 1National Engineering Research Center for Southwest Endangered Medicinal Materials Resources Development, Guangxi Botanical Garden of Medicinal Plants, Nanning, People’s Republic of China; 2National Chinmedomics Research Center, National TCM Key Laboratory of Serum Pharmacochemistry, Chinmedomics Research Center of State Administration of TCM, Laboratory of Metabolomics, Department of Pharmaceutical Analysis, Heilongjiang University of Chinese Medicine, Harbin, People’s Republic of China; 3Engineering Research Center of Innovative Traditional Chinese, Zhuang and Yao Materia Medica, Ministry of Education, Guangxi University of Chinese Medicine, Nanning, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fangfang Wu, Email wffttn@163.com Xiaonan Yang, Email nannangood33@163.comPurpose: Yuquan capsule (YQC) is a well-known proprietary Chinese medicine used for the treatment of type 2 diabetes mellitus. The aim of this study was to investigate the potential mechanism and efficacy of YQC in the treatment of T2DM by means of metabolomics.Methods: Thirty-two male SD rats were randomly divided into four groups of control, type 2 diabetic mellitus (T2DM), metformin (Met), and YQC. Establishment of the T2DM model by high-fat diet (HFD) and streptozotocin (STZ). Fasting blood glucose (FBG) and weight were measured weekly, urine output was collected and recorded. The blood, kidney, pancreas, and liver tissue samples were collected at the end of the experiment. Blood samples were analyzed with methods of ELISA, pancreas, and liver tissues were analyzed by pathological sections, and serum was analyzed by metabolomics using ultra-performance liquid chromatography quadrupole time-of-flight coupled with mass spectrometry (UPLC-Q/TOF-MS).Results: It was observed that YQC could reduce blood glucose levels by modulating blood lipid and transaminase indices, and by diminishing the concentration of inflammatory factors within hepatic and pancreatic tissues. Furthermore, YQC restores homeostasis by regulating lipid and amino acid metabolism, engaging 21 biomarkers and 10 metabolic pathways.Conclusion: YQC has the capacity to enhance blood lipid and transaminase levels, suppress the expression of inflammatory factors, and foster the homeostatic progression of metabolic circulation in rats with T2DM.Keywords: type 2 diabetes mellitus, mechanism, lipid metabolism, blood lipid balance